Analysis Of Leadership And Colleagues On Employee Job Satisfaction With The Work Environment As An Intervening Variable In CV. ANUGERAH PRIMA METALINDO - Michael Gunawan; Wilchan Robain; M. Chaerul Rizky (Yayasan Multidimensi Kreatif, 2025)
The success of an organization depends heavily on the quality of human resources in it. Competency-based human resource development aims to improve productivity, work quality, and customer satisfaction, which ultimately benefits the organization. Employees who are satisfied with their work will be more committed, productive, and highly dedicated to the company, while employees who are dissatisfied with their work tend to experience turnover and decreased productivity. This study aims to analyze the influence of leadership and co-worker relationships on employee job satisfaction through work environment factors. The results of the study show that leadership has a positive and significant effect on the work environment in CV. Anugerah Prima Metalindo, as well as colleagues who have a positive and significant influence on the work environment. In addition, leadership and colleague relationships also have a positive and significant effect on employee job satisfaction. The work environment also has a positive and significant influence on employee job satisfaction. This study also reveals that leadership and colleague relationships have a positive and significant influence on employee job satisfaction through the work environment as a connecting variable in CV. Anugerah Prima Metalindo.